PROBLEMATIKA PEMBIAYAAN MUDHÂRABAH DI PERBANKAN SYARIAH INDONESIA - Hadi, Ahmad Chairul (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2011)
Islamic bank was originally constructed as a non-usurious bankwith profit and loss sharing in all its operational mechanism. However, its progress in fulfilling the function of banks as intermediaries (financial intermediary), all types of business law legalized of syar'î based non-profit-sharing such as trade, leasing, and other services into products of Islamic banks. In fact, theoretically financing products with profit sharing schemecan be more economically prosperous society. This article discusses the problems and solutions system sharing (mudhârabah) in the scheme of financing in Islamic banks.DOI: